Expectations and Preferences of Parents and Adolescents Regarding Feedback of Individual Genetic Findings in an HIV-TB Genomic Research Project in Botswana - Ralefala, Dimpho (Department of Medicine, 2023)
Background: There has been tremendous progress in the use of genomics1 in biomedical research and medical care since the launch of the Human Genome Project in 1990. However, it has also introduced new ethical challenges regarding the feedback of findings generated in genomic sequencing. While some would argue in support of the return of individual findings generated from genomics research, participants' preferences regarding which findings should be fed back differs. Most literature discusses feedback of findings in high income countries and very few address this issue in lower and middle-income countries (LMICs). As a result, it remains unclear whether and how individual findings from genomic studies in Africa should be fed back, who should provide these results and when. Methods: In order to contribute to addressing this gap, an empirical study was conducted to explore expectations and preferences for feedback of individual genetic findings in an HIV-TB genomics research project in Botswana. A qualitative study methodology involving deliberative focus group discussions (dFGDs) and in-depth interviews (IDIs) was used. Participants for this study were adolescents involved in an HIV-TB genomics study being conducted at the Botswana-Baylor Children's Clinical Centre of Excellence (BBCCCE). Parents and caregivers of children enrolled in that same genomic study were also enrolled in this study. A total of 93 participants (44 adolescents and 49 parents and caregivers) were enrolled in 12 dFGDs (6 groups of adolescents and 6 groups of parents and caregivers). Each group of participants met twice within a week, resulting in a total of 24 dFGD meetings. Participants of the dFGDs and in-depth interviews were selected purposively. Additionally, indepth interviews were conducted with 12 dFGD participants (6 adolescents and 6 parents or caregivers). The dFGDs and IDIs were conducted in Setswana, audio-recorded, transcribed and translated into English. Data were imported into NVivo 12 and analysed using the framework approach for qualitative data analysis. Results: The study findings revealed that participants' desire to receive individual genetic results is underpinned by their cultural values, mainly solidarity and reciprocity. Participants viewed research participation as a mutual relationship and considered the return of research results to be one way of reciprocating their efforts. This seems to be underpinned by the principle of Ubuntu which advocates for solidarity and reciprocity within communities. Participants noted that when reciprocity obligations are respected, participants feel valued and expressed that not respecting reciprocity expectations could undermine participants' trust and participation in future studies. Almost all participants wanted to receive individual genetic results. While parents and caregivers wanted to receive individual genetic results regardless of their severity, preventability or actionability, adolescents were reluctant to receive results for genetic conditions that are severe and non-preventable, especially if they are also unactionable. Participants advanced different reasons for feedback of results including for awareness, improving lifestyle, accepting one's' situation, and preparing for the future. The findings also reveal the importance of taking into account participants' context, relations and empowerment when making decisions about whether and which results ought to be fed back. When asked about practical considerations for feedback of results, both adolescents and parents expressed that they would prefer to receive individual genetic results in person, with adolescents preferring researchers to provide feedback, while parents preferred feedback from doctors associated with the study. Adolescents and parents both expressed that feedback should be supported by counselling, but they differed on the timing of feedback. Most participants shared that they would like to be informed about the possibility of discovering individual genetic results during the consent process and that consent be obtained for feedback during the enrolment process. They further expressed that in cases where prior consent to feedback was not obtained, then participants should be re-contacted where lifesaving genetic information is discovered. Participants emphasized the need for researchers to ensure that participants' decisions regarding feedback of results are well-informed. Autonomy, transparency, and communication were identified as key values to uphold during the consent process. Conclusion: In conclusion, expectations of solidarity and reciprocity could translate into an obligation to feedback selected individual genetic results in African genomics research. Decisions on practicalities for feedback of results should take into account participants' context and considerations of participants' preferences. For example, in settings like BBCCCE it might be feasible for the study team to relay participants' results to treating doctors in the same centre, while also organising counselling services if necessary. However, in cases where a study is done in a public facility with limited resources, that could be difficult to implement. Consequently, researchers may have to take up the responsibility of feeding back individual results as well as providing genetic counselling in such settings. To make these decisions, researchers should engage with relevant stakeholders including policymakers and local Institutional Review Boards (IRBs) so as to make informed decisions regarding the feasibility and acceptability of their approach to feedback of results. Obtaining participants' consent for feedback of results is important to ensure that their rights and wellbeing are protected in research. This is critical in building trust relationships between participants and researchers. Lastly, although this study is focused in Botswana, these findings could also be generalised to similar contexts in Africa and provide an authoritative voice to H3Africa to be able to mandate projects with potential to generate individual genetic results to make provisions to feedback these results to study participants.